1998
DOI: 10.1159/000040869
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Monitoring Response to Treatment of Hepatosplenic Candidiasis in Patients with Acute Leukemia Using Magnetic Resonance Imaging

Abstract: Hepatosplenic candidiasis (HSC) is a morbid complication encountered in immunocompromised individuals, especially, those being treated with intensive chemotherapy protocols for acute leukemia. Immediate recognition of this complication and initiation of appropriate treatment is crucial in order to control the infection, decrease the morbidity and mortality, and avoid delays in treatment of the underlying condition. The definitive diagnosis requires either positive blood cultures for yeasts in the presence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…Diagnosis is generally supported by a compendium of clinical [46], radiological [47][48][49] and mycological evidence [50]. Efforts made to include the results of serological tests in this compendium have generally failed, despite consistent improvements in the sensitivity and specificity of these tests, particularly those detecting candidaderived molecules such as D-arabinitol [26], glucans [25] and mannan [24,51].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis is generally supported by a compendium of clinical [46], radiological [47][48][49] and mycological evidence [50]. Efforts made to include the results of serological tests in this compendium have generally failed, despite consistent improvements in the sensitivity and specificity of these tests, particularly those detecting candidaderived molecules such as D-arabinitol [26], glucans [25] and mannan [24,51].…”
Section: Discussionmentioning
confidence: 99%
“…Biphasic liver CT scan as an alternative shows lesions with typical central contrast enhancement and a peripheral double ring in the arterial phase in adults [17]. As radiation exposure should be considered, particularly in children, high-resolution ultrasonography is a reasonable initial alternative for screening, despite a lower level of sensitivity than those of CT and MRI [18][19][20][21]. As the lesions of disseminated candidiasis are more readily observed when associated with inflammation, imaging modalities are best performed in oncology patients and haematopoietic stem cell transplant recipients after recovery from neutropenia.…”
Section: Chronic Disseminated or Hepatosplenic Candidiasismentioning
confidence: 99%
“…Although MRI achieved higher diagnostic accuracy of HSF than CT and ultrasonography in previous studies, 12,13,24 CT scan and ultrasonography are more widely used and more cost-effective in Taiwan. Karthaus et al 25,26 reported serial ultrasonography up to twice a week had the same detection rate and reliability of hepatosplenic abscess compared with CT scan and MRI.…”
Section: Demonstrated the Presence Of Hepatosplenicmentioning
confidence: 82%